Arcane 11 - Donzel-Gargand, Bernard, 1945- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1990)
The different sound materials of the work come from commercial synthesizers (DX7 / D50). The SAMI (Computer Assisted Music Support System), developed by Bernard Donzel-Gargand and Adrien Lefevre (IRCAM), allowed me to create this music. This instrument offers various access commands such as: - joy-sticks, - photocells, - pedals, who can each, according to our imagination, drive real-time music parameters (change of timbre, velocity, frequency according to modes, ranges, series, tempo, speed etc .). The final version of the work is the result of mixing a 3-part score. An Arcane is a mysterious, secret operation of alchemists. Are we not alchemists of the sound world, we musicians? Eleven is, for the Arabs, the number of the knowledge of God, which passes through 11 stages: - the will corresponding to self-control, - abstinence and music that bring purification, - time, stage of the wander between self-awareness and God, - the image of God reflected in every creature, - the end of worry, - perfect tranquility and permanent ecstasy, - the outburst out of oneself, - the possibility of going up to God, - the loss of the will, - the return trip with God, - permanent contemplation giving the power to work miracles.